Serum Gel Formulation of Mundu Fruit Extract (Garcinia dulcis (Roxb.) Kurz) as Antioxidant and Anti-elastase - Valeria; Neneng Siti Silfi Ambarwati; Yesi Desmiaty; Yuslia Noviani; Yulia Triyani (Fakultas Farmasi Universitas Andalas, 2024)
UV radiation can generate ROS, thereby damaging neutrophils, leading to the uncontrolled release of elastase, and causing aging. This study intends to examine the antioxidants and anti-elastase activity of the skin of Garcinia dulcis (Roxb.) Kurz fruit in serum gel extract preparation. The methods used in this research are microwave-assisted extraction and antioxidants using the ABTS (2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) method. Three formulas were made with 100 x IC50, 200 x IC50, and 300 x IC50. The test results for the three formulas showed the best antioxidant and anti-elastase activity values in formula 3, with IC50 values ​​of 66.26 ppm and 111.48 ppm. This indicates that the higher the extract concentration in the formulation provides better activity in the serum gel preparation. In the third formulation, evaluation observations were made on the preparation, and a pH value close to the skin’s pH was produced, namely in formula 3. Therefore, it can be concluded that the Mundu fruit peel extract has antioxidant and anti-elastase activity. The extract is applied to cosmetic preparations and still provides good antioxidant and anti-elastase activity results.